DEVELOPMENT OF A QUALITATIVE RESEARCH PROJECT IN NURSING AND HEALTH IN TEN STEPS - Castañeda, Raúl Fernando Guerrero; Machain, Pedro Aguilar (Cogitare Enfermagem, 2024)
Objective: to describe the recommendations for developing a qualitative research project in nursing and health in ten steps. Development: brief theoretical communication, built from reflective integration based on a literature review on qualitative research in nursing and health during 2024. Ten steps and recommendations stand out: define the idea and develop research questions; define the object of study; explore literature; choose and delve deeper into the epistemic approach; develop the theoretical-philosophical framework; select the method and approach; define the methodological path; define qualitative criteria for methodological rigor; be creative and revolutionary; and write and generate ideas, question and analyze. Conclusion: the formulation of a qualitative research project in nursing and health can be developed based on recommendations that guide researchers’ critical reflection, which will allow the integration of a sustained and rigorous research project proposal.